Propuesta de metodologías amigables con el medio ambiente para el control de la erosión hídrica en la microcuanca hidrográfica del Río Chimborazo, Localizada en el cantón Riobamba, Provincia de Chimborazo. - Pacheco Díaz, Silvana Magdalena (2013)
Suggest environmentally friendly methods to prevent water erosion in the hydrographic basin of the river Chimborazo, located in Canton Riobamba, Chimborazo Province, and set by the environmental impact assessment whether it is feasible to implement this project. Considering also all existing within this watershed factors, because when there are no proposals of this type in this region. For this reason the importance of this thesis and its implementation.